Synthesis and thermal properties investigation of colloidal nanoparticles and their applications - Noroozi, Monir (2013)
Colloidal nanoparticles (NPs) have unique thermal, optical, electronic, and chemical properties that are extremely different from bulk materials due to their size. The central concerns in their preparation are the control of particle size, shape and the prevention of NPs agglomeration. In this relation, the objectives of the study are firstly, to green synthesize of silver nanoparticles (Ag NPs) in narrow distribution using green solvent and microwave (MW) irradiation as a cheap and fast method; secondly, to investigate the thermal diffusivity and the thermal effusivity of nanofluids by using PE technique; and thirdly, to increase the PE signal in optical fiber-thermal wave cavity (OF-TWC) technique by using Ag NPs film due to its strong optical absorption. In the first study, the fabrications of Ag NPs in water and ethylene-glycol as solvents at various MW reaction times were carried out. In the second study, a mathematical model of the multilayer samples by using thermal wave (TW) interferometry approach was developed and both Back- and Front-PE configurations were derived from it as special cases, the thermal diffusivity and thermal effusivity of nanofluids and the PE sensor were evaluated. In the third study, the optical fiber tip was coated by Ag NPs to increase the PE signal in OF-TWC technique. By increasing the MW irradiation time from 20 to 90 s the concentration of Ag NPs slightly increased and the NPs size increased from 7 to 12 nm. The Ag NPs prepared in ethylene glycol were more dispersed, more concentrated and more stable than those prepared in water. The observed difference may be ascribed to the high boiling points, molecular weight and dielectric loss of the ethylene glycol. The thermal diffusivity of nanofluids was investigated by using the Back-PE configuration in OF-TWC set-up. The linear increase in thermal diffusivity with Ag NPs volume fractions in nanofluids from 0 to 0.5 vol% has been observed, the highest value was 1.571×10-3 cm2/s. However, the highest value of thermal diffusivity reduced to 1.456 ×10-3 cm2/s after 3.h time of leave, due to the NPs agglomeration in solution. The higher thermal diffusivity of Al2O3 nanofluid prepared by probe sonication than by bath sonication is due to higher dispersion of NPs in water. The fragmentation by laser irradiation at low concentration reduced the agglomerated size of NPs and increased the thermal diffusivity values, e.g., from 1.444×10-3 to 1.498×10-3 cm2/s for Al2O3 and from 1.477×10-3 to 1.537×10-3 cm2/s for CuO nanofluid from 0 to 90 min irradiation. The Front-PE configuration was designed by using a PVDF film sensor to measure thermal effusivity of the sensor itself in Thermally Thick regime, and of the nanofluids for both Thermally Thick and Thermally Very Thick regimes. The thermal effusivities of the sensor obtained from the normalized amplitude, 464.5 Ws1/2m−2K−1, and phase 479.1 Ws1/2m−2K−1 are close to each other, and the experimental error is less than 0.3.% and differs by less than 4.% to literature. The thermal effusivity of the solvents such as deionized water, ethylene glycol and olive oil obtained from the methods showed good agreement with literatures but reduced in the presence of NPs. The TW generator comprised of Ag NPs-coated onto an optical fiber end surface, showed a significant enhancement of PE signal in OF-TWC setup owing to surface Plasmon resonance and to strong optical absorption in Ag NPs. Laser irradiation to the surface melts the NPs and connects them together to form a continuous smooth Ag film on the optical fiber end surface.